Value Co-creation for sustainable consumption and production in the sharing economy in China. (20th January 2019) - Ma, Yuge; Rong, Ke; Luo, Yining; Wang, Yong; Mangalagiu, Diana; Thornton, Thomas F.
Abstract: Sustainable Consumption and Production (SCP) has traditionally treated consumption and production as separate domains of economic activities with different solutions for sustainability. In the emerging sharing economy, consumption activities are more and more integrated into the production process of shared goods and services, which provides novel arenas for sustainability in cities. Increasingly, these sharing business models are aiming to solve long-standing urban sustainability problems, such as insufficient daily transport, and its problems of polluttion. In this article, we integrate theories of the sharing economy, value co-creation and SCP to argue that the emergent forms of value co-creation between consumers and sharing businesses provide new opportunities for SCP. We use two emergent and representative sharing mobility businesses in China – a bike-sharing scheme called Mobike and an electric-vehicle-sharing scheme called EVCARD – as case studies to analyze the sustainability potentials of value co-creation. The social, behavioral, economic, and infrastructural obstacles encountered in realising such potentials are also identified. Based on these empirical results, we propose a framework to conceptualize the emerging patterns of value co-creation between governments, sharing business firms, and consumers in the sharing economy. We highlight the importance of understanding value co-creation for development of SCP theory and practice to guide the evolving sharing economy.